Supply chain performance measurement of olive oil industry with KPIs. (2015) - Kumar, Rupesh
Supply chain performance of a particular type of supply chain can be determined using certain key performance indicators (KPIs) of that industry. This paper aims to present a supply chain performance index for Portuguese olive oil industry on the basis of identifying performance indicators. The indicators were identified on the basis of survey and informal discussion with the management team of olive mills in Portugal. A questionnaire was developed for getting responses from mill managers, heads, engineers, and other employees of different departments of olive mills using a five-point Likert scale. Further, the key performance index of the particular olive mill is calculated using the proposed formula by Cleveland et al. (1989) on the basis of three weight criteria. This index can be used to make a suitable benchmark for the best olive industries which will help managers of other supply chains to measure and compare their supply chain performance with benchmarked supply chains. The result shows the weak and strong performance indicators of the olive mill in order to know their fallback situation and manage their on-time production requirements. Additionally, each performance indicator can be improved with the use of suggestive IT solutions.